The US dollar and its challenges: American hegemony in the 21st century. (6th July 2018) - Costigan, Thomas; Cottle, Drew
Abstract: Since World War Two, the United States dollar became and remains the global reserve currency. This status in international trade and investment has given the US the ability to exercise hegemonic power around the world. In recent years, there have been attempts by competitor nations notably China, Russia, and Iran to replace the dollar's exclusivity in bilateral trade. Their intention is to undermine the ability of the US to continue as the world's hegemon. It is argued that this outcome is unlikely to be achieved in the near term, because of the continuing reliance on the US dollar.